Comparison of pulsed actinomycin D and 5‐day actinomycin D as first‐line chemotherapy for low‐risk gestational trophoblastic neoplasia. Issue 2 (16th August 2018) - Mu, Xiyan; Song, Liang; Li, Qingli; Yin, Rutie; Zhao, Xia; Wang, Danqing
Abstract: Objective: To compare the treatment outcome and cost‐effectiveness of pulsed actinomycin D (Act‐D) and 5‐day Act‐D in patients with low‐risk gestational trophoblastic neoplasia (GTN). Method: The present retrospective study included patients with low‐risk GTN who received pulsed Act‐D or 5‐day Act‐D as first‐line chemotherapy at West China Second Hospital, Chengdu, China, between January 1, 2016, and December 31, 2017. Complete remission rates, mean number of treatment courses, and adverse events were compared, and a cost‐effectiveness analysis was performed. Results: The study included 34 patients treated with pulsed Act‐D and 26 patients treated with 5‐day Act‐D. Overall complete remission was observed in 21 (62%) patients in the pulsed Act‐D group and 19 (73%) patients in the 5‐day Act‐D group ( P =0.355); the mean number of treatment courses were 5.1 and 5.3, respectively ( P =0.686). When Act‐D failed, patients in each group required 4.9 and 4.6 courses, respectively, of a multi‐agent regimen ( P =0.545). No major adverse events were observed but moderate adverse events were more frequent in the pulsed Act‐D group ( P =0.011). The 5‐day Act‐D regimen was more expensive compared with pulsed Act‐D regimen (US$7504.33 vs $5541.79), with an incremental cost‐effectiveness ratio of $64 557.08 per avoidance of treatment failure. Conclusion: Pulsed Act‐D was more cost‐effective than 5‐day Act‐D and could be preferred when considering Act‐D as chemotherapy for low‐risk GTN. Abstract : Pulsed actinomycin D was more cost‐effective than 5‐day actinomycin D and could be considered when prescribing actinomycin D to treat low‐risk gestational trophoblastic disease.